2020
DOI: 10.22605/rrh5754
|View full text |Cite
|
Sign up to set email alerts
|

Patient and provider perspectives on eHealth interventions in Canada and Australia: a scoping review

Abstract: Introduction: Despite the promises of universal health care in most developed countries, health inequities remain prevalent within and between rural and remote communities. Remote health technologies are often promoted as solutions to increase health system efficiency, to enhance quality of care, and to decrease gaps in access to care for rural and remote communities. However, there is mixed evidence for these interventions, particularly related to how they are received and perceived by health providers and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 0 publications
5
62
0
Order By: Relevance
“…50 Identi ed disadvantages of mHealth apps are mostly technological, lack of face-to-face contact, training of users and resources. 51 Our study showed positive changes towards healthier lifestyle habits with better physical and psychological well-being, and even found lower levels of perceived and biological stress among participants. However, we need the follow-up study which will be able to reveal the factors that are necessary for the e-solution to be successful in health changes.…”
Section: Discussionsupporting
confidence: 45%
“…50 Identi ed disadvantages of mHealth apps are mostly technological, lack of face-to-face contact, training of users and resources. 51 Our study showed positive changes towards healthier lifestyle habits with better physical and psychological well-being, and even found lower levels of perceived and biological stress among participants. However, we need the follow-up study which will be able to reveal the factors that are necessary for the e-solution to be successful in health changes.…”
Section: Discussionsupporting
confidence: 45%
“…While much of the information that rural cancer survivors require is similar to those in metropolitan cities, the need for information to assist with the practical and emotional issues caused by travelling for cancer care is something that urban survivors do not have to face. An increased use of telehealth services for routine check‐ups may alleviate some of the challenges associated with travelling for healthcare services 46,47 and avoid the barriers to accessing local survivorship care and support 19 . Additionally, carefully designed rural‐specific websites or peer‐led YouTube videos have been shown to be an acceptable method of delivering rural specific information to cancer survivors 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Identified benefits of using eHealth services for primary care provision include reducing the burdens that come with travelling long distances, increasing access to care, and cost savings across various domains. 9 Despite perceived benefits, implementation is often non-existent, difficult, or slow. Cost, technological issues, and slow acceptance by providers is a recurring issue for successful long-term eHealth implementation.…”
Section: Current Knowledgementioning
confidence: 99%
“…Cost, technological issues, and slow acceptance by providers is a recurring issue for successful long-term eHealth implementation. 9,10 Teletriage and virtual triage are eHealth initiatives proposed to mitigate rural healthcare gaps.…”
Section: Current Knowledgementioning
confidence: 99%